Hubungan Pengetahuan Ibu dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Krueng Barona Jaya - Nur Azizah; Khaira Rizki; Wildan Seni (Lembaga Pengembangan Kinerja Dosen, 2025)
Growth resulting from chronic hunger from birth to two years of age is called stunting. Children who experience stunting are more susceptible to problems related to their cognitive and motor development, as well as an increased risk of disease. The purpose of this study was to determine the relationship between maternal knowledge and the prevalence of stunting in toddlers in the service area of ​​the Krueng Barona Jaya Community Health Center. The purpose of this study was to investigate the relationship between maternal knowledge and child stunting. Quantitative research using cross-sectional and correlational methodologies. A sample of 59 respondents was selected using a proportional sampling design technique. The time period for this investigation was May 8-16, 2025. This study used univariate and bivariate analysis. The research data were collected using a closed questionnaire paradigm with multiple-choice questions, and the Chi-Square test was used for analysis. A P-value of 0.047 (P < 0.05) indicates a relationship between maternal knowledge and the prevalence of stunting in toddlers in the work area of ​​the Krueng Barona Jaya Community Health Center. Research shows a link between stunting in toddlers and maternal knowledge. Stunting is more likely to affect toddlers born to mothers with less knowledge than those with more knowledge. Mothers of toddlers are advised to receive regular counseling and educational materials to raise awareness and reduce the prevalence of stunting.